2014
DOI: 10.1002/glia.22679
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of raloxifene-induced upregulation of glutamate transporters in rat primary astrocytes

Abstract: Raloxifene (RX), a selective estrogen receptor modulator (SERM), exerts neuroprotection in multiple clinical and experimental settings. Astrocytic glutamate transporters GLT-1 (EAAT2) and GLAST (EAAT1) are the main glutamate transporters in the central nervous system, taking up most of excess glutamate from the synaptic cleft to prevent excitotoxic neuronal death. Since drugs targeting astrocytic glutamate transporters to enhance their expression and function represent potential therapeutics for neurodegenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 67 publications
3
71
0
5
Order By: Relevance
“…Glutamate uptake assays were performed as described previously 63 to the reaction media to provide a final concentration of 100 nM glutamate. The reaction was continued for 10 minutes at 37°C and terminated by washing three times with ice-cold PBS, immediately followed by cell lysis in 1 ml of 1 N sodium hydroxide.…”
Section: Glutamate Uptake Assaymentioning
confidence: 99%
“…Glutamate uptake assays were performed as described previously 63 to the reaction media to provide a final concentration of 100 nM glutamate. The reaction was continued for 10 minutes at 37°C and terminated by washing three times with ice-cold PBS, immediately followed by cell lysis in 1 ml of 1 N sodium hydroxide.…”
Section: Glutamate Uptake Assaymentioning
confidence: 99%
“…Earlier studies have also suggested that transcriptional regulation of EAAT1 might be different from that of EAAT2 because the mTORPI3k/Akt signaling cascade induced only EAAT2 expression (27,28). Some studies show that NF-B might also play a critical role in the regulation of EAAT1 expression induced by EGF, TGF-␣, and raloxifene in rat primary astrocytes (19,21). However, the precise relationship between NF-B and EAAT1 has yet to be characterized.…”
mentioning
confidence: 99%
“…The EAAT1 promoter is stimulated by growth factors such as EGF and TGF-␣, leading to enhancement of EAAT1 mRNA expression (17,18), as well as protein levels (19,20). Estrogen and selective estrogen receptor modulators, such as tamoxifen and raloxifene, also enhance EAAT1 mRNA and protein levels (21,22). The transcription factor NF-B has been reported to be a critical positive regulator of GLT-1/EAAT2 and mediates the stimulatory effects of various modulators such as ceftriaxone (23), EGF (24,25), tamoxifen, and raloxifene (21,26) on EAAT2 expression.…”
mentioning
confidence: 99%
See 2 more Smart Citations